Опыт количественной оценки газоносности угленосных толщ на базе формационного анализа - Майборода, А.А.; Анциферов, В.А.; Иванов, Л.А.; Савченко, А.В.; Шпак, В.Ю. (Наукові праці УкрНДМІ НАН України, 2012)
Наведено результати практичного застосування «Методичних рекомендацій щодо оцінки газоносності вугленосних товщ Донбасу на базі формаційного аналізу» на шахти ім. В. М. Бажанова ДП «Макіїввугілля». The results of practical use of “Methodological recommendations for evaluation of gas content in coalbearing series of the Donets Coal Basin based on the formation analysis” at the minefield of V. M. Bazhanov Mine (State-Owned Company “Makeevugol”) are described.